EFFECTS OF THE RELATIVIZATION OF RES JUDICATA (Reflection and Critique Law Magazine, 2024)
This article discusses the importance of the res judicata institute in the pacification of interests and controversies. As it is a secular institute, its historical origins, its continuous changes in the face of new paradigms of law and its permanence in the legal system are analyzed. Doctrinal positions in favor of legal certainty are compared - that is, the maintenance of the res judicata dogma, with the exception of the typical hypotheses that rule out the validity of the judgment - and those that defend the relativization of res judicata in view of the principle of justice, since unjust sentences must not persist at any time. Finally, the generalized effects that this phenomenon generates in the legal system are verified, such as increased litigation, legal uncertainty and adverse selection of demands.